Biomechanical evaluation of bovine stifles stabilized with an innovative braided superelastic nitinol prosthesis after transection of the cranial cruciate ligament. Issue 7 (26th August 2021) - Constant, Caroline; Braïlovski, Vladimir; Wagnac, Éric; Petit, Yvan; Desrochers, André; Nichols, Sylvain
Abstract: Objective: To determine the stability bovine stifles stabilized with nylon or nitinol superelastic prostheses after transection of the cranial cruciate ligament (CCL). Study design: Ex vivo study. Sample population: Stifles ( n = 15) harvested from adult bovine cadavers. Methods: The stifles were randomly assigned pairwise to a ligament reconstruction technique (n = 5): (1) and (2) Hamilton's technique using a prosthesis made of 24 nitinol strands (0.39 mm) braided at 40°or single 600‐lb test nylon implant, and (3) nitinol prosthesis placed in femoral and tibial bone tunnels (bone‐to‐bone). Craniocaudal tibial translation at ±2000 N was applied to the tibia, and mediolateral angular displacement via measured under torsional tibial loading at ±60 Nm on three occasions: intact CCL, transected, and stabilized. Outcomes were evaluated with a mixed effect linear model for repeated measures. Results: Bone‐to‐bone using nitinol was the only repair that decreased tibial translation after CCL transection ( p = .001) with a 23% change magnitude compared with intact CCL. Hamilton was the only stabilization reestablishing angular displacement, similar to intact CCL ( p = .109 and .134 for nitinol and nylon). Bone‐to‐bone nitinol stabilization decreased angular displacement after CCL‐transection with an 8% change magnitude ( p = .040) without returning to normal values. Conclusion: CCL replacement with nylon did restore joint stability. Nitinol prostheses passed through single femoral and tibial bone tunnels (bone‐to‐bone) were the only techniques reducing tibial translation. Clinical significance/impact: Bone‐to‐bone stabilization with a nitinol prosthesis may be considered as an alternative to nylon for CCL replacement in cattle. These results provide evidence to justify clinical evaluation in cattle undergoing CCL replacement.